2017
DOI: 10.1007/s11761-017-0205-1
|View full text |Cite
|
Sign up to set email alerts
|

QoS-aware optimal and automated semantic web service composition with user’s constraints

Abstract: Automated semantic web service composition is one of the critical research challenges of service-oriented computing, since it allows users to create an application simply by specifying the inputs that the application requires, the outputs it should produce, and any constraints it should respect. The composition problem has been handled using a variety of techniques, from Artificial Intelligence (AI) planning to optimization algorithms. However no approach so far has focused on handling three composition dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…Reference [21] focuses on the dynamic composition of Web services, taking into account users' requirements, especially non-functional requirements. In this work, a new QoS-based framework proposed allowing to elaborate Web services composition solutions using planning graph and Harmony Search (HS) algorithm.…”
Section: Relevant Work Related To Requirements-driven Web Servicmentioning
confidence: 99%
“…Reference [21] focuses on the dynamic composition of Web services, taking into account users' requirements, especially non-functional requirements. In this work, a new QoS-based framework proposed allowing to elaborate Web services composition solutions using planning graph and Harmony Search (HS) algorithm.…”
Section: Relevant Work Related To Requirements-driven Web Servicmentioning
confidence: 99%
“…In this research, Web Service Specification Language (WSSL) is utilised to provide the description capabilities. Bekkouche et al (2017) proposed an improved Harmony Search algorithm aiming to the optimised result respect the global QoS constraints. Zhang et al (2010) developed a WEEE recycling system based on the cloud.…”
Section: Networked Weee Management and Trackingmentioning
confidence: 99%
“…The system architecture of a WEEE cyber-physical system centred by a digital twin is shown in Figure 3. The system is established based on the SOA, in which both the electronic device and its digital twin are considered as the service objectives (Baryannis, Kritikos, and Plexousakis 2017;Bekkouche et al 2017). As mentioned, the digital twin plays as the bridge between the physical world and the cyber world.…”
Section: System Architecture For a Digital Twin-enabled Cyber-physicamentioning
confidence: 99%
“…In addition, some other methods have also been adopted to solve the problem of service composition. For instance, Bekkouche et al [31] described a novel approach based on a Harmony Search algorithm that addressed functional requirements and nonfunctional requirements simultaneously through a fitness function, to select the optimal or near-optimal solution in semantic web service composition; Jatoth et al [32] proposed a novel MapReduce-based Evolutionary Algorithm with Guided Mutation that lead to a better Big service composition with better solution and execution time; Labbaci et al [33] put forward a deep learning approach for dynamic QoS based service composition which got promising results compared with existing QoS prediction techniques. These pieces of work have shown that the service composition problem 4 Complexity is an essential part of the current research on intelligent manufacturing.…”
Section: Related Workmentioning
confidence: 99%